Clinical evaluation of treatment with hook plate in patients with acromioclavicular joint dislocation - Büyükceran, İsmail; Çinka, Hikmet; Yurtbay, Alparslan; Coşkun, Hüseyin Sina; Yıldırım, Abdurrahman Murat; Keskin, Davut (The European Research Journal, 2023)
Objectives: Treatment of acromioclavicular joint dislocations vary. In this study, we aim to examine the functional results of patients who underwent hook plate fixation due to dislocation of acromioclavicular joint. Methods: We retrospectively observed 21 patients who had been treated with hook plate due to dislocation of acromioclavicular joint. At follow up, Constant-Murley scoring system was performed for shoulder function evaluation, while radiological results were performed by X-ray. Results: Seventeen of these patients were male and four were female. Eleven of these patients had Rockwood type 5 joint dislocation and ten had Rockwood type 3 joint dislocation. The mean age was 36.7 ± 13.37 years (range: 19-61 years). The mean follow-up period was 27.3 ± 19.3 months (range: 10-59). Constant-Murley shoulder scoring was excellent in 18 patients (93.6) and good (82.5) in 3 patients. While one patient had wound site infection and one patient had plate broken, no one had any neurological damage. Except for the failed implants, plate removal was not performed because the patients did not have plate-related complaints. At follow-up, it was observed that the acromioclavicular joint was in the reduced position on direct radiographs. Conclusions: We observed good clinical and functional results for the treatment of acromioclavicular joint dislocation with hook plate treatment. The hook plate method is a safe and effective method in the acute treatment of type 3-5 injuries according to the Rockwood classification.